2005
DOI: 10.1016/j.ejcnurse.2005.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Introducing the Cardibra: A Randomised Pilot Study of a Purpose Designed Support Bra for Women Having Cardiac Surgery

Abstract: This innovative device may offer therapeutic benefits to women following cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…Muscular tenderness was found in relation to the cervical injury (C 5 ‐Th 1 ) [21]. Pain on the breasts and pain wearing a bra, very common in the CPSP patients in our study and previously reported [22,23] in relation to CPSP, are also associated with low cervical damage [24].…”
Section: Discussionsupporting
confidence: 70%
“…Muscular tenderness was found in relation to the cervical injury (C 5 ‐Th 1 ) [21]. Pain on the breasts and pain wearing a bra, very common in the CPSP patients in our study and previously reported [22,23] in relation to CPSP, are also associated with low cervical damage [24].…”
Section: Discussionsupporting
confidence: 70%
“…Large bra (cup size D and D+) and medium bra (cup C) sizes are associated with an increased risk of deep sternal wound infection following cardiac surgery because the weight of large unsupported breasts place a higher lateral traction on the midline incision [63][64][65]. Literature suggests that women's pain discomfort, and possibly wound complications, are reduced with the use of a supportive bra [66,67].…”
Section: Skin Stress Due To Hypertrophy Mamma In Womenmentioning
confidence: 99%
“…Published reports [19][20][21] are focused on the use of these garments for stabilization of the sternum, improved approximation of sternal wounds, and comfort. The Women's Recovery from Sternotomy-Extension Study determined that female patients experience postoperative pain for up to a year after their cardiac surgery, and a larger chest circumference is a risk factor.…”
Section: Surgical Bramentioning
confidence: 99%
“…The Women's Recovery from Sternotomy-Extension Study determined that female patients experience postoperative pain for up to a year after their cardiac surgery, and a larger chest circumference is a risk factor. 20 The postsurgical brassiere offered at www.ccnonline.org our hospital was not constructed to accommodate forward breast expansion. The fabric did not stretch, and most importantly, the edges were abrasive, minimally elastic, and constrictive.…”
Section: Surgical Bramentioning
confidence: 99%